Desalination of salted duck egg white assisted by gelatin: Foaming and interface properties of the mixed system. (March 2022) - Dai, Yalei; Zhao, Jingyun; Liang, Hongshan; Deng, Qianchun; Wan, Chuyun; Li, Bin; Zhou, Bin
Abstract: The reutilization of salted duck egg whites is still an important challenge facing the egg product industry. Efficient desalination of salted duck egg white is an effective way to make high-value use of the by-product in the food manufacturing. In this work, benefit from the thermoreversible properties of gelatin (GEL), salted duck egg white (SDEW) was blended with GEL to desalt after forming gels (4 °C). After the temperature was restored, the egg white was recovered to liquid after desalting, which still maintained the functional properties. Using this simple method, the desalination rate reached from 92.85% to 95.75% after 6 h soaking, and the protein loss rate was about 0.197–0.366%. Compared with the control group (only containing SDEW or GEL), salted egg white/gelatin mixed solution after desalination (DDG) had higher foaming capability and foaming stability at different concentrations of gelatin and salted egg whites. This indicated that egg whites still had good foaming properties after desalination. The following interfacial properties demonstrated DDG could adsorb to the air-water interface and formed a viscoelastic surface layer. Additionally, DDG (1 mg/mL) prepared from egg white and gelatin had a unique interfacial expansion rheological behavior. Herein, this study provides a new path for SDEW desalination through physical technology, which of course broadens the utilization of salted duck egg white. Graphical abstract: Image 1 Highlights: A simple and mild method for salted egg white desalination assisted by gelatin. The foaming and interface properties of desalted duck egg white/gelatin mixtures were investigated. The desalted duck egg white/gelatin mixtures provide high foaming capability and good foaming stability. The foaming properties is consistent with the interface characteristics and structures.